1949
DOI: 10.1172/jci102073
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Influenza Virus and Bacteria in the Etiology of Pneumonia 12

Abstract: Evidence is accumulating that influenza virus plays a role in the etiology of certain pneumonias generally considered to be primarily bacterial in origin. The earliest recorded observations (1, 2) describe influenza as a mild self-limited disease of the upper respiratory tract which progressed occasionally in certain individuals to produce more serious symptoms involving the pulmonary tissue. Soon after the discovery of bacteria, clinicians (3) pointed out that pneumonia caused by streptococci, staphylococci a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1949
1949
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
(25 reference statements)
1
15
0
1
Order By: Relevance
“…The results of this investigation are in general similar to those of the only other large-scale studies on pneumonia and influenza yet reported (Finland et al 1948;Maxwell et al 1949 A point of contrast between the results of the present investigation and those of the Baltimore workers lay in the nature of the bacteria present in the sputum or lung. All of the virus-positive cases of pneumonia identified in Baltimore during the epidemic yielded pneumococci, whereas the staphylococcus was an important organism in our own cases and particularly in the fatal illnesses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of this investigation are in general similar to those of the only other large-scale studies on pneumonia and influenza yet reported (Finland et al 1948;Maxwell et al 1949 A point of contrast between the results of the present investigation and those of the Baltimore workers lay in the nature of the bacteria present in the sputum or lung. All of the virus-positive cases of pneumonia identified in Baltimore during the epidemic yielded pneumococci, whereas the staphylococcus was an important organism in our own cases and particularly in the fatal illnesses.…”
Section: Discussionsupporting
confidence: 85%
“…Several observers have drawn attention recently to a possible connexion between influenza and pneumonia (Commission on Acute Respiratory Diseases, 1945;Finland, Ory, Meads & Barnes, 1948;Maxwell, Ward & van Metre, 1949). It has of course long been known that a general relationship exists between influenza and pneumonia in that an increase in incidence of pneumonia occurs during outbreaks of influenza, but the exact role of the virus infection in such cases is obscure.…”
Section: (With 3 Figures In the Text)mentioning
confidence: 99%
“…In one of these patients the effusion was present prior to admission. Typical X-ray pictures are presented in Figures 17,19,20 Cough, chest pain, dyspnea, and cyanosis graded in severity from 0 to + + +. 224 findings.…”
Section: Methodsmentioning
confidence: 99%
“…They described the recovery of virus from a febrile man who then developed pneumococcal pneumonia 7 days into his convalescence and died (6). Once the viral etiology of influenza was firmly established, a series of detailed studies on the pathology, bacteriology, and epidemiology of bacterial pneumonia during influenza followed over the next decade (47,97,120,132,145,156). Influenza A and B viruses were both shown to predispose to bacterial infections, with S. pneumoniae and S. aureus as the most often cited invaders.…”
Section: Recognition Of Dual Infectionsmentioning
confidence: 99%